Determination of Gross Alpha and Beta Activity in Water: (A Case Study of Gombe Metropolis). (Journal of Basic and Applied Research in Biomedicine, 2022)
A study on the “Determination of Gross Alpha and Beta activitity in Water” in Gombe metropolis was carried out. Nuclides are unstable elements that are spontaneously emitting nuclear radiation in an attempt to attain the nuclear structure of the stable elements. Humnan exposure to these radiation beyond certain limit can cause serious health problems. Radionuclides can be found in air, water and soil. This study investigated the gross alpha and beta activity in water from Gombe metropolitan. Gross alpha and beta activity is a measure of the total amount of natural radioactivity in a water sample attributable to the radioactive decay of alpha or beta particles emitted from natural decay series. The gross alpha and beta activity is used to create assurance on the level of nuclear contamination in water for drinking and other domestic use. The World Health Organization (WHO) standard for alpha and beta activity in water 100 Bqm-3 . The resuts obtained in this study varies between 0 – 0.045 Bqv/I and 0.659 – 11.580 Bq/I for alpha and beta radiation respectively. Comparison of these results with the WHO standards shows that the gross alpha and beta activity in the water in Gombe metropolitan is far beow WHO satndards. This indicates the safety of the water in the study area for drinking and other domestic applications.